Heat transfer of a coil-tube heat exchanger in the freeboard zone of a rice husk fluidized-bed combustor - Chokphoemphun, S.; Eiamsa-ard, S.; Promvonge, P.; Thongdaeng, S.; Hongkong, S. (My University, 2021)
This research presents an investigation on heat recovery from a fluidized-bed combustor by using coil-tube heat exchangers positioned inside the freeboard zone. Rice husk was used as a fuel at a constant mass flow rate of 8 kg/h. Heat recovery experiments were performed at four different air mass flow rates (6.0248, 6.8077, 7.8163, and 8.8646 kg/h) using coil-tube heat exchangers wrapped around with steel wires in three different configurations (2_Coil wires, 4_Coil wires and Full length). Air was supplied to the coil-tube heat exchanger with two different air flows corresponding to flue gas flow: co-flow and counter-flow. The results showed that the outlet temperature tended to decrease with an increase in air flow rate in the coil-tube heat exchanger. The outlet temperatures obtained from the system with co-flow were greater than the one with counter-flow by 7–17 °C (2–15%) depending on the coil-tube heat exchanger configuration. The heat transfer rates in heat recovery process were in the range of 279–425 J/s. In addition, it was found that the heat transfer rate and the outlet temperature of the air from the coil-tube heat exchanger increased with an increase in the number of coil wires wrapped around the outer surface of the coil-tube heat exchanger.
Keywords: Coil-tube; Combustion; Fluidized bed combustor; Heat recovery; Rice husk fuel